1977
DOI: 10.1007/bf00416954
|View full text |Cite
|
Sign up to set email alerts
|

Die Beeinflussung der Knochenheilung durch hochkonzentriertes Fibrin

Abstract: The influence of a biological tissue glue--based on fibrinogen clotting--on bone healing has been investigated in animal experiments. Standardized cortical defects in the tibiae of rabbits were closed with a plug of homologous or heterologous fibrin. The course of restoration has been studied using histological techniques, x-ray examinations and isotopes (Ci 99 TC). Heterologous fibrin delays bone formation, due to a local immune response. Homologous fibrin on the other hand cubances and accelerates sprouting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 6 publications
0
6
1
1
Order By: Relevance
“…These quantitative data are in contrast to previous reports of improved bone formation and accelerated vascularization as a results of FS-treatment (Bosch et al 1977, 1979, 1980, Arbes et al 1981.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These quantitative data are in contrast to previous reports of improved bone formation and accelerated vascularization as a results of FS-treatment (Bosch et al 1977, 1979, 1980, Arbes et al 1981.…”
Section: Discussioncontrasting
confidence: 99%
“…Correspondence: Ulf Lucht, Mirabellevej 7, Denmark In bone transplantation, fibrin sealant (FS) has been reported to improve a homogeneous incorporation of the implant due to an accelerated vascularization (Bosch et al 1977, 1979, 1980, Arbes et al 1981, Bosch 1981. Special indications for adding FS to the graft have been claimed to be poor osteogenic potency of the recipient site, chronic osteomyelitis and implantation of an allograft (Bosch 1981).…”
Section: No Effects On Blood Flow and Bone Formation In Dogsmentioning
confidence: 99%
“…143 Similarly, Bösch et al found that while heterologous fibrin impaired the bone healing process, due to a local immune response, homologous fibrin accelerated the growth of capillary vessels and connective tissue cells, which resulted in rapid new bone formation. 144 Other researchers argued that the addition of a fibrin sealant to coral granules limited the infiltration of osteoprogenitor cells into the implantation area. 145 This was further confirmed by an observed delay in bone formation in femoral defects of rats implanted with fibrin-containing PLGA/calcium phosphate scaffolds.…”
mentioning
confidence: 99%
“…However, with the use of heterologous fibrin sealant (human sealant used in rabbit experiments), markedly delayed vascular ingrowth can be [5]. Vascularization occurs weeks later than in the control groupafter fibrinolysis of the fibrin clot.…”
Section: Bone Graftingmentioning
confidence: 99%